Disproportionality analysis of adverse events associated with pacritinib: a real-world study based on FDA Adverse Event Reporting System (FAERS) database - Zhang, Huiling; Huang, Yaping; Ke, Chengjie; Chen, Maohua (Frontiers in Oncology, 2025)
IntroductionPacritinib, a selective Janus kinase (JAK) inhibitor, is approved for the treatment of myelofibrosis in adults with severe thrombocytopenia. However, its safety profile in real-world populations remains unclear. The aim of study is provided a comprehensive profile of pacritinib's safety by evaluating the adverse events (AEs) using a real-world pharmacovigilance database.MethodsData from the FDA Adverse Event Reporting System (FAERS) database, spanning from the first quarter of 2022 to the second quarter of 2024, served as the basis for this analysis. To identify potential AE risk signals, several disproportionality analysis methods were applied, including the reporting odds ratio, the proportional reporting ratio, the multi-item gamma Poisson shrinker, and the Bayesian confidence propagation neural network.ResultsA total of 4,304,335 AE reports were collected from the FAERS, with 1,940 reports identifying pacritinib as the primary suspect drug. Significant disproportionality was observed in the following system organ classes: gastrointestinal disorders, investigations, and surgical and medical procedures. Common preferred terms were identified, including diarrhea, fatigue, death, nausea, platelet count decreased, and hemoglobin decreased. Notably, 26 off-label AEs were also identified.DiscussionOur study would provide valuable insights for the post-marketing safety surveillance and assessment of pacritinib, and guide its clinical practice.